Communication tools with residents in Polish municipalities with cohabitation (term of office 2014-2018) - Sidor, Monika; Kuć-Czajkowska, Katarzyna; Wasil, Justyna (Wydawnictwo Naukowe WNPiD UAM, 2019)
The paper describes the tools for communication with residents used by municipalities. The basis for paper preparation was qualitative (extended interviews) and quantitative (a question chosen from a questionnaire) research conducted within a selected group of municipalities with cohabitation during the term of office between 2014 and 2018. The aim of the paper is to determine whether and what kind of tools for communication with residents are applied by municipal authorities. How effective are these tools? Does cohabitation type: conflict or peaceful, influence the channel through which residents acquire information? What impact will the changes introduced in 2018 in self-government law (the goal was, among others, to broaden the transparency of self-government work) have on the methods of communication with residents used by the authorities?

W artykule scharakteryzowano wykorzystywane przez gminy narzędzia komunikowania z mieszkańcami. Podstawą do przygotowania artykułu były badania jakościowe (wywiady pogłębione) i ilościowe (wybrane pytanie z kwestionariusza ankiety) przeprowadzone w wyodrębnionej grupie gmin z koabitacją w kadencji 2014-2018. Celem artykułu jest wskazanie czy i jakiego rodzaju narzędzia komunikowania z mieszkańcami stosują władze gminy? Jaka jest skuteczność tych narzędzi? Czy rodzaj koabitacji: konfliktowa vs. pokojowa ma wpływ na sposób informowania mieszkańców? Jak wprowadzone w styczniu 2018 zmiany w prawie samorządowym (których celem było m.in. zwiększenie transparentności funkcjonowania władz samorządowych) wpłyną na sposób komunikowania się władz z mieszkańcami?
Narzędzia komunikacji z mieszkańcami w polskich gminach z koabitacją (kadencja 2014-2018)
Keywords: municipality; cohabitation; communication tools; internet; gmina; koabitacja; narzędzia komunikowania; Internet